'Real-life' analysis of the role of antifungal prophylaxis in preventing invasive aspergillosis in AML patients undergoing consolidation therapy: Sorveglianza Epidemiologica Infezioni nelle Emopatie (SEIFEM) 2016 study. (14th January 2019) - Del Principe, Maria Ilaria; Dragonetti, Giulia; Verga, Luisa; Candoni, Anna; Marchesi, Francesco; Cattaneo, Chiara; Delia, Mario; Potenza, Leonardo; Farina, Francesca; Ballanti, Stelvio; Decembrino, Nunzia; Castagnola, Carlo; et al.
Abstract: Background: We evaluated the incidence of proven/probable invasive aspergillosis (IA) and the role of antifungal prophylaxis (AP) in a 'real-life' setting of patients with AML receiving intensive consolidation therapy. Methods: Cases of IA, observed during consolidation in adult/paediatric patients with AML between 2011 and 2015, were retrospectively collected in a multicentre Italian study. Results: Of 2588 patients, 56 (2.2%) developed IA [43 probable (1.7%) and 13 proven (0.5%)]. IA was diagnosed in 34 of 1137 (2.9%) patients receiving no AP and in 22 of 1451 (1.5%) who were given AP ( P =  0.01). Number-needed-to-treat calculation indicates that, on average, 71 patients should have received AP (instead of no AP) for one additional patient to not have IA. Initial antifungal therapy was 'pre-emptive' in 36 (64%) patients and 'targeted' in 20 (36%) patients. A good response to first-line therapy was observed in 26 (46%) patients, mainly those who received AP [16 of 22 (73%) versus 10 of 34 (29%); P =  0.001]. The overall mortality rate and the mortality rate attributable to IA by day 120 were 16% and 9%, respectively. In multivariate analysis, age ≥60 years (OR = 12.46, 95% CI = 1.13–136.73; P =  0.03) and high-dose cytarabine treatment (OR = 10.56, 95% CI = 1.95–116.74; P =  0.04) independently affected outcome. Conclusions: In our experience, AP appears to prevent IA from occurring during consolidation. However, although the incidence of IA was low, mortality was not negligible among older patients. Further prospective studies should be carried out particularly in elderly patients treated with high-dose cytarabine to confirm our data and to identify subsets of individuals who may require AP.